« Lumière vivante » : le discours naturaliste sur la phosphorescence de la mer au XIXe siècle - Azoulai, Juliette (Studia Romanica Posnaniensia, 2018)
The phosphorescence of the sea has aroused much questioning since antiquity and numerous studies address the topic in the 19th century, when this phenomenon (today referred to as bioluminescence) is given a biological explanation. Raising admiration, wonder, but also scientific controversy, the bright sea is a common motif, frequently reappearing in scientific travel writing, research studies in marine biology, popular science and literary texts. This paper examines the imaginary component which underlies these different texts and seems attached to the depiction of living light.